Answer:
-3+x=x+4
Step-by-step explanation:
Pls Mark Brainliest
Answer:
SNITCHY SNATCH
Step-by-step explanation:
I actually don't know how to show how to graph it. Sorry. But I can give a few coordinates. For y < 1/3x + 3: (-1,2 2/3) (0,3) (1,3 1/3). For y > -2/3x - 3: (-1,-2 1/3) (0,-3) (1,-3 2/3).
5 would be the answer to it
![\huge\bold\green{Answer:-}](https://tex.z-dn.net/?f=%5Chuge%5Cbold%5Cgreen%7BAnswer%3A-%7D)
Simplifying
36c2 + -84cd + 49d2 = 0
Reorder the terms:
-84cd + 36c2 + 49d2 = 0
Solving
-84cd + 36c2 + 49d2 = 0
Solving for variable 'c'.
Factor a trinomial.
(6c + -7d)(6c + -7d) = 0
Subproblem 1
Set the factor '(6c + -7d)' equal to zero and attempt to solve:
Simplifying
6c + -7d = 0
Solving
6c + -7d = 0
Move all terms containing c to the left, all other terms to the right.
Add '7d' to each side of the equation.
6c + -7d + 7d = 0 + 7d
Combine like terms: -7d + 7d = 0
6c + 0 = 0 + 7d
6c = 0 + 7d
Remove the zero:
6c = 7d
Divide each side by '6'.
c = 1.166666667d
Simplifying
c = 1.166666667d
Subproblem 2
Set the factor '(6c + -7d)' equal to zero and attempt to solve:
Simplifying
6c + -7d = 0
Solving
6c + -7d = 0
Move all terms containing c to the left, all other terms to the right.
Add '7d' to each side of the equation.
6c + -7d + 7d = 0 + 7d
Combine like terms: -7d + 7d = 0
6c + 0 = 0 + 7d
6c = 0 + 7d
Remove the zero:
6c = 7d
Divide each side by '6'.
c = 1.166666667d
Simplifying
c = 1.166666667d
Solution
c = {1.166666667d, 1.166666667d}
<h2>I HOPE IT HELPS ♥️</h2>